The complexities of PKCα signaling in cancer. (May 2021) - Black, Adrian R.; Black, Jennifer D.
Abstract: Protein kinase C α (PKCα) is a ubiquitously expressed member of the PKC family of serine/threonine kinases with diverse functions in normal and neoplastic cells. Early studies identified anti-proliferative and differentiation-inducing functions for PKCα in some normal tissues (e.g., regenerating epithelia) and pro-proliferative effects in others (e.g., cells of the hematopoietic system, smooth muscle cells). Additional well documented roles of PKCα signaling in normal cells include regulation of the cytoskeleton, cell adhesion, and cell migration, and PKCα can function as a survival factor in many contexts. While a majority of tumors lose expression of PKCα, others display aberrant overexpression of the enzyme. Cancer-related mutations in PKCα are uncommon, but rare examples of driver mutations have been detected in certain cancer types (e. g., choroid gliomas). Here we review the role of PKCα in various cancers, describe mechanisms by which PKCα affects cancer-related cell functions, and discuss how the diverse functions of PKCα contribute to tumor suppressive and tumor promoting activities of the enzyme. We end the discussion by addressing mutations and expression of PKCα in tumors and the clinical relevance of these findings.